Anti-Impf-Bewegung und Verschwörungsnarrative in der Tschechischen Republik - Miroslav Mareš (Totalitarismus und Demokratie, 2022)
Abstract The author deals with the use of conspiracy narratives by actors of the anti-vax movement in the Czech Republic during the Covid-19 pandemic in the years 2020–2022. The general development of the pandemic and the governmental measures are described, and the milestones of the anti-vax movement are identified. Conspiracy narratives are categorized in relation to traditional or new issues and to the national or global scope. Specific attention is paid to the anti-Semitic conspiracy narratives interconnected with part of the anti-Vax movement. Various kinds of conspiracy narratives were used in the Czech Republic, and they mobilized the anti-vax movement; however, its political results and impact on elections were limited.